CURRENT DIRECTIONS IN COACHING RESEARCH - Gilbert Wade (Revista Iberoamericana de Psicología del Ejercicio y el Deporte, 2011)
The purpose of this article is to provide a brief overview of some current directions in North American coaching research. Based on our review of the literature and awareness of the field, we selected coaching effectiveness and coach development as two dominant research themes for review. Although focused on North American research, evidence suggests that these trends are not exclusive to the North American context. The conceptual frameworks and research designs being used to conduct North American research on coaching effectiveness and coach development also appear to be widely adopted in coaching research around the world (Rangeon, Gilbert, & Bruner, 2011). This is not surprising given the increased global interest in the professionalization of sport coaching (Duffy et al., 2011).